2018
DOI: 10.1111/tbed.12947
|View full text |Cite
|
Sign up to set email alerts
|

The emergence of a highly pathogenic porcine reproductive and respiratory syndrome virus with additional 120aa deletion in Nsp2 region in Jiangxi, China

Abstract: Highly pathogenic porcine reproductive and respiratory syndrome (HP-PRRS), which emerged in China in 2006, was characterized by high fever, high morbidity and high mortality. The causative agent of the disease was a highly pathogenic variant of porcine reproductive and respiratory syndrome virus (also called HP-PRRSV), which has a discontinuous deletion of 1 + 29 amino acids (aa) in the Nsp2 coding region, compared to classical PRRSV. In 2014, fattened pigs on a pig farm in Jiangxi Province suffered from clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…In addition, MLV-derived field isolates and recombinants from MLV and wild-type strains have been isolated [ 26 , 62 ]. Moreover, some MLV-like isolates (NT1, JX2014T2 and XJ17-5) are highly virulent viruses determined by animal challenge studies [ 24 , 63 , 64 ]. Therefore, more attention should be paid to PRRS vaccine safety.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, MLV-derived field isolates and recombinants from MLV and wild-type strains have been isolated [ 26 , 62 ]. Moreover, some MLV-like isolates (NT1, JX2014T2 and XJ17-5) are highly virulent viruses determined by animal challenge studies [ 24 , 63 , 64 ]. Therefore, more attention should be paid to PRRS vaccine safety.…”
Section: Discussionmentioning
confidence: 99%
“…Whether these highly homologous HP-PRRSV variants with novel deletion in nsp2 have distinct virulence becomes an interesting question. Notably, a recent study identified that a new isolate JX2014T2, which contains the same 150-amino-acid deletion in nsp2 , is highly pathogenic to piglets [24]. However, the similarity between the JX2014T2 and our isolates was unable to be determined because the JX2014T2 sequence is not available.…”
Section: Discussionmentioning
confidence: 92%
“…Marc-145 cells were infected with 200 median tissue culture infectious doses (TCID 50 ) of XJ17-5 and JSTZ1712-12, respectively. The infected Marc-145 cells were fixed at 24 h post infection and evaluated by IFA according to the standard procedure [24]. Porcine reproductive and respiratory syndrome virus (PRRSV)-specific murine mAb 15A1 (1:500 dilution) against the N protein was used as the primary antibody, while the Dylight 594 (Goat anti-mouse IgG, 1:1000, Invitrogen) was used as the secondary antibody.…”
Section: Figurementioning
confidence: 99%
“…These were observed e.g. in virulent Chinese PRRSV strains [108]. Interestingly, some nsp2 deletions were shown to reduce the expression of IL-1 beta [99].…”
Section: Crucial Areas Of Investigation Into the Prrsv-host Relationshipmentioning
confidence: 88%